FAKTOR RISIKO PAPARAN BISING TERHADAP NILAI AMBANG DENGAR PEKERJA DI TERMINAL KARGO BANDARA AHMAD YANI SEMARANG - Hana Nuriy Rahmawati; Ari Suwondo; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
The increasing speed of threshold hearing value for each individual is determined by external factors and internal factors. The external factors are noise intensity, the frequency of sound, the distance between workers and noise source, years of work and exposure time. In other hands, the internal factors are the history of the illness which is related to a hearing system, the history of using ototoxicity medicine and also age. Cargo Terminal in Airport is a place to loading and unloading of cargo handling from consumers and then forwarded to ground handling Airport and vice versa. The design study that is conducted by quantitative with cross sectional approach. The total population in Cargo Terminal is 44 workers. The sampling method is conducted by purposive sampling with inclusive criteria, which produce 33 samples. Data collecting conducted by inquiries filled by the subjects and also measurement using Audiometer and Noise Dosimeter. Measurement of threshold hearing value using Audiometer shown that 36,4% out of 33 respondents experiencing hearing disorders. Thus, noise measurement using Noise Dosimeter in Cargo Terminal shown that theintensity exposure level of noise are 75,3 and 78,9 dB(A).  Results of statistical test using chi-square, the correlating factors are age (p-value=0,047,PR=2,800), ear trauma (p- value=0,040,PR =3,333), noise in residential environment (p-Value=0,040,PR =3,333).  Age, ear trauma and noise in residential environment are the correlating factor towards workers threshold hearing level in Cargo Terminal Ahmad Yani Semarang Airport. The management are suggested to regularly measure the intensity exposure of noise with minimal every 3 months and also provide a soundproof  rest area for workersto rest inside Cargo Terminal.